Neutrophil membrane-coated PLGA nanoparticles promoting the repair of myocardial ischemia-reperfusion injury in mice - Jing CHEN; Yanan SONG; Zheyong HUANG; Junbo GE (Zhongguo Linchuang Yixue)
ObjectiveTo explore the role and related mechanism of neutrophil membrane-coated poly(lactic-co-glycolic acid) (PLGA) nanoparticles (Neu-NP) in cardiac repair after acute myocardial ischemia-reperfusion (MI/R) injury in mice. MethodsThe male C57 mouse model of acute MI/R injury was established and randomly divided into three groups: PBS control group (injection of 200 μL PBS), NP treatment group (injection of 0.5 mg/mL NP 200 μL), and Neu-NP treatment group (injection of 0.5 mg/mL Neu-NP 200 μL). Neutrophil membranes were extracted and fused with PLGA nanoparticles to construct biomimetic Neu-NP. The in vivo homing ability of Neu-NP was assessed using ex vivo imaging technology in the MI/R injury model, and the expression levels of tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6) in the myocardium were measured using enzyme linked immunosorbent assay one day and three days after administration. Echocardiography was used to determine cardiac function indicators of MI/R injured mice 28 days post-administration. Immunofluorescence staining was used to observe angiogenesis repair and inflammatory cell infiltration in mouse heart tissue. ResultsNeu-NP, engineered by integrating neutrophil membranes with nanoparticles, inherited surface receptors (TNF-αR and IL-6R) and functioned as decoys for inflammatory targeting. Compared with the PBS control group and NP treatment group, the secretion levels of TNF-α and IL-6 in the damaged myocardium of the Neu-NP treatment group were significantly decreased one and three days after administration (P＜0.05); 28 days after administration, the cardiac ejection fraction in the Neu-NP treatment group was significantly higher than that in the other two groups (P＜0.05). Immunofluorescence staining indicated a significant increase in the proportion of angiogenesis in the myocardial infarction area and a significant reduction in inflammation cell infiltration (P＜0.05). ConclusionsNeu-NP plays an important role in cardiac tissue repair after MI/R injury by alleviating inflammatory factors in the damaged area and promoting angiogenesis.